Clinico-histopathological observations of pigeons (Columba Livia) suffering from Newcastle disease in northern Bangladesh - Parvez, Md Najmul Hassan; Islam, Md Reazul; Akter, Most Tahera Dil; Sarder, Md Jalal Uddin (Asian Journal of Medical and Biological Research, 2017)
A survey was conducted to study clinical signs, gross and histopathological lesions in pigeons with naturally occurring Newcastle disease (ND). For this purpose, 45 pigeon farms of the Rajshahi, Natore and Pabna districts were conducted during from July 2015 to June 2016. Among these, 17(37.78%) farms showed clinical signs of Newcastle disease, including mainly greenish white mucoid diarrhoea and nervous signs with high morbidity and mortality. Morbidity was 90% and mortality was 100%. Diarrhoea, the most common clinical sign observed, was present in 48.28% of the affected pigeons, followed by nervous signs (27.59%), shivering (24.14%). Postmortem examination of affected birds showed lesions mainly in proventriculus, liver, lungs and kidneys. Histopathological changes were also observed in lungs, liver, and proventriculus. The results showed that the Newcastle disease virus was widespread in pigeons locally and caused high mortality rate. It is concluded that pigeon fanciers of northern Bangladesh do not maintain the regular preventive measures or vaccination against ND is being adopted to control the disease. Asian J. Med. Biol. Res. March 2017, 3(1): 134-139